The Effect of Earthworm Meal Supplementation in the Diet on Quail’s Growth Performance in Attempt to Replace the Usage of Fish Meal - Prayogi , Heni Setyo (International Journal of Poultry Science, 2011)
This study was conducted to evaluate the effect of supplementation of different level of earthworm meal in the diet on quail’s growth performance; feed consumption, Body Weight (BW) gain and feed conversion in attempt to replace the usage of fish meal. One day old quails of both sexes (80) were randomly allotted to 16 groups with 5 quails in each group (4 dietary treatments, 4 replicates). The treatments consisted of; 0% of earthworm meal and 15% of fish meal (control), 5% of earthworm meal and 10% of fish meal, 10% of earthworm meal and 5% of fish meal and 15% of earthworm meal and 0% of fish meal in the diet. Each diet was formulated to have the same content of protein (±24.40%) and calorie (±2950 kcal/kg). The data were statistically analyzed by the One Way of ANOVA and continued by the Duncan’s new Multiple Range Test (DMRT) for significant results. The result showed that the feed consumption was decreased due to higher percentage of earthworm and it was significantly different (p<0.01) compared to the control group. However, the BW gain was decrease steeply on the higher percentage of earthworm (15%) or no fish meal in the diet. It was concluded that the supplementation of 10% of earthworm in the diet gave a good growth performance of the quail because it has low feed conversion and high BW gain.